2002
DOI: 10.1254/jjp.90.281
|View full text |Cite
|
Sign up to set email alerts
|

Method for Simultaneous Recording of the Prostatic Contractile and Urethral Pressure Responses in Anesthetized Rats and the Effects of Tamsulosin

Abstract: We simultaneously recorded the prostatic contractile and urethral pressure responses to electrical stimulation (ES) of the hypogastric nerves (HGNs) or phenylephrine in anesthetized rats and studied the effects of tamsulosin on these responses. At 0.01 and 0.1 mg/kg, i.v., tamsulosin inhibited the prostatic responses to ES of the HGNs in a dose-dependent manner, while at 1 microg/kg, i.v., it reduced the response to phenylephrine (0.01 mg/kg, i.v.) to about 26% of the nonantagonized level. These inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The in vivo prostate tension was evaluated according to a previous study . Briefly, rats were anesthetized with urethane (1.8 g/kg, ip), and the prostate was exposed through a midline abdominal incision.…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo prostate tension was evaluated according to a previous study . Briefly, rats were anesthetized with urethane (1.8 g/kg, ip), and the prostate was exposed through a midline abdominal incision.…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo prostate tension was evaluated as described by Kontani & Shiraoya [33]. Adult male rats (120 days old, 500 g weight) were anesthetized with urethane (1.5 g/kg, sc) and the prostate ventral lobes were tied with a cotton thread and attached to an isometric force transducer under 9.8 mN resting tension.…”
Section: Methodsmentioning
confidence: 99%
“…In various mammals, including humans, semen can be obtained by stimulation of the sympathetic and parasympathetic nerves destined for ejaculatory tissues (Watanabe et al, 1988;Brindley et al, 1989;Kolbeck and Steers, 1992;Kontani and Shiraoya, 2002). Traumatic or postsurgical disruption of sympathetic pathways innervating the seminal tract is a cause of ejaculatory dysfunction (anejaculation or retrograde ejaculation) in men (May et al, 1969;Pocard et al, 2002).…”
Section: Efferent Pathways and Finalmentioning
confidence: 99%
“…Both ␣ 1 -and ␣ 2 -adrenoreceptors have been identified in urethra of various species, being mainly located in smooth muscle cells (␣ 1 ) and submucosa (␣ 2 ) (Monneron et al, 2000). Pharmacological investigations showed that contractions of the seminal tract and accessory sex glands elicited by sympathomimetic agents were blocked, at least partially, by ␣ 1 -adrenoreceptor antagonists (Stjernquist et al, 1983;Terasaki, 1989;Kolbeck and Steers, 1992;Kontani and Shiraoya, 2002). Cholinomimetic drugs are known to induce contraction of sex glands through stimulation of muscarinic receptors (Lepor and Kuhar, 1984;Terasaki, 1989).…”
Section: Neuropharmacology Of Ejaculationmentioning
confidence: 99%